2018
DOI: 10.1016/j.neurobiolaging.2018.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Premarin has opposing effects on spatial learning, neural activation, and serum cytokine levels in middle-aged female rats depending on reproductive history

Abstract: Menopause is associated with cognitive decline, and hormone therapies (HTs) may improve cognition depending on type and timing of HTs. Previous parity may influence cognition in later life. We investigated how primiparity and long-term ovariectomy influence cognition, neurogenesis, hormones, cytokines, and neuronal activation in middle-aged rats in response to Premarin, an HT. Nulliparous and primiparous rats were sham-ovariectomized or ovariectomized, administered vehicle or Premarin 6 months later, and all r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 104 publications
(104 reference statements)
0
13
0
Order By: Relevance
“…These findings indicate that not all estrogens increase neurogenesis in the hippocampus. Intriguingly, spatial training and age influence how Premarin, a hormone therapy comprised of 50% estrone sulphate and 0.1% estradiol sulphate, increases neurogenesis [230, 233]. Premarin increases survival of new neurons in radial-maze trained rats but not in cage controls [230].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicate that not all estrogens increase neurogenesis in the hippocampus. Intriguingly, spatial training and age influence how Premarin, a hormone therapy comprised of 50% estrone sulphate and 0.1% estradiol sulphate, increases neurogenesis [230, 233]. Premarin increases survival of new neurons in radial-maze trained rats but not in cage controls [230].…”
Section: Introductionmentioning
confidence: 99%
“…In middle-aged nulliparous or primiparous rats (i.e. rats who have never given birth to a litter and rats who have had one litter, respectively), lower doses of Premarin decreased survival of new neurons in rats that were also trained in the Morris Water Maze [233]. Recent work also suggests that long-term exposure to estradiol, but not DPN or PPT, increases survival of new neurons in the hippocampus of female mice [234], suggesting either the involvement of other ERs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We expected irregular estrous cycling in at least a proportion of sham-operated mice as they were middle-aged at testing. Mice in persistent diestrus, persistent estrus, or that displayed abnormalities in the length or order of estrous cycle stages were all classified as irregularly cycling, as we have done previously (Galea et al, 2018). Ovariectomized mice were also lavaged to control for potential effects of the procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence for long-term cognitive changes as a result of parity in humans is somewhat equivocal; however, in animal models, it has been demonstrated that reproductive experience leads to enhanced cognitive function, particularly with memory and learning (reviewed in 144 ). Alongside this, reproductive experience in animal models induces positive neuroplasticity, such as increases in synaptic proteins, 147,148 a higher level of hippocampal neurogenesis [149][150][151] and a general slowing down of age-dependent decline in neurogenesis. 144 Insulin has been shown to promote neuroplasticity both in development and in the adult, contributing to a healthy brain.…”
Section: B E Yond Preg Nan C Y and L Ac Tati O Nmentioning
confidence: 99%